IEG Review of World Bank Assistance for Financial Sector Reform. - Effron, Laurie (World Bank e-Library., 2006)
This evaluation presents an independent assessment of the Bank's support for financial sector reforms over the period FY93-03. It assesses the extent to which the objectives of Bank assistance were achieved, including reducing government ownership of financial intermediaries, decreased market concentration, increased competition and efficiency, healthier and more stable financial intermediaries, and deeper, more developed financial systems. It also examines Bank support for financial sector reforms in countries under crisis.